Protein Profile of Mozzarella Cheese Produced by Lime Juice Acidification (Jurnal Ilmu dan Teknologi Hasil Ternak, 2009)
A research about the production of Mozzarella cheese with lime juice has been done to study the protein profile of this cheese. The method used in this research was experimental and designed by completely randomized design. The treatments were variation of lime juice concentration, namely: K1 = 1.9 %, K2 = 2.1 %, K3 = 2.3 %, K4 = 2.5 %, K5 = 2.7 %, and K6 = 2.9 % (v/v). The protein profile of this cheese acidified by using the concentration of 1.9 â€“ 2.9 % lime juice gived differences profile. The best treatment was 1.9 % concentration of lime juice, its gave the highest value. Â  Keywords: protein profile, Mozzarella cheese, acidification, lime juice